A Survey Of Mine Ventilation Practices ? Introduction - Pierre Mousset-Jones (Society for Mining, Metallurgy & Exploration, 1986)
A questionnaire was sent out to three classes of mines to determine the extent of the heat problem in U.S. and Foreign underground mines. The following list shows the replies received from this questionnaire, however not all the known hot mines in the US replied. A complete listing of the results can be seen in Appendix I. 1) US coal mines - 37 replies 2) US non coal mines - 23 replies 3) Foreign non coal mines - 36 replies. At the present time there are approximately eleven non coal and one coal mine in the US experiencing heat problems which require special efforts to maintain an acceptable working place climate. However since the survey was completed some of them have been placed on standby. The Mine Safety & Health Administration (MSHA) does not have any specific regulations relating to heat stress. Informally the American Conference of Governmental Industrial Hygienists guidelines are followed which use wet bulb globe temperature (WBGT) with values ranging from 26.7°C to 31.1°C for a moderate workload, and different rest regimes. An MSHA report (Misaqi 1976) recommended that conditions should not exceed 26.1°C WBGT for men and 24.4°C WBGT for women. However, quite recently the organizations involved with planning two of the proposed nuclear waste repositories in the United States, have opted for the criteria of an air cooling power of 300 w/m2, and a WBGT of 27'C respectively.